DEVELOPING ENGLISH WRITING MATERIAL USING EGRA TECHNIQUE OF DESCRIPTIVE TEXT FOR GRADE X STUDENTS OF SMA NEGERI 6 MEDAN - Wahyuni Safitri Burhan; Sumarsih Sumarsih; Zainuddin Zainuddin (Universitas Negeri Medan, 2019)
Nowadays, English become a language that can give a significant impact in many aspects such as education and communication. Therefore people are demanded to master in language including students. For example researcher finding at class x of SMAN 6 Medan student have low competence in writing skill. This study aimed to Develop English Writing Material Using EGRA Technique of Descriptive Text for Grade X. The subject of this research was students’ grade X MIA 2 of SMAN 6 Medan consists of 34 students. Tomlinso (1990) state the EGRA is an effective technique to teach grammar in writing sentence. The letter standing for Exposure, Generalization, Reinforcement, and Application. This research used the model of Research and Development (R&D)of Brog and Gall (2003) has six stages: there are (1) Gathering information, (2) Analyzing data, (3) Designing new writing material using EGRA, (4) Evaluating or validating new writing material by experts, (5) Revising, (6) Final product. The instruments of data collection were syllabus, questioner and interview. The data was gathered by administering interview to the teacher and distributing questioner to the students. The first design writing material of this research consists of three units: “hi iam arief” (describing people), “Mount Lesuer National Park” (describing place), “Water Castle” (describing bulding). The score of validating from expert there are: (1) English lecture, the score of content is 25, score of language is 12, score of presentation is 27,and score of graphic is 9 and the average of score material assessment were 3,17 in categorize good. (2) English teacher English lecture, the score of content is 26, score of language is 12, score of presentation is 25,and score of graphic is 12 and the average of score material assessment were 3,26 in categorize very good. Based on the result of the validation of the experts, there are two aspects that needed to revised such as to revise some grammatical mistakes and unclear the exercise. The final product of writing material consists of three units: “hi I am arief” (describing people), “Mount Lesuer National Park” (describing place), “Water Castle” (describing building). In each unit have four sections provided there are Exposure, Training, Grammar and WritingKey words: writing skill, EGRA technique, Research and Development (R&D)